The impact of the small and medium enterprise support programmes on the livelihoods of micro-entrepreneurs using sustainable livelihood framework : a case study of Enterprise Mongolia Project Phase 2 by United Nations Development Programme in Mongolia : a thesis presented in partial fulfillment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University, Palmerston North, New Zealand - Ganbold, Mongoljin (Massey University, 2016)
The aim of this research is to explore the impact of Enterprise Mongolia Project EMP-2 project on the livelihoods of the Small and Medium Entrepreneurs (SMEs) using Sustainable Livelihood Framework (SLF) in the context of Mongolia. Both qualitative and quantitative research methods are used in order to carry out this research. The study started firstly with the review of existing literature followed by field research to explore in depth rural livelihoods and SMEs in Mongolia. The research is conducted in two phases. The first phase comprises examining the case study of Enterprise Mongolia Project 2 (EMP-2) and discusses the role of SME support programmes in poverty reduction. The second phase of the research method comprised of conducting in-depth semi-structured interviews with 20 entrepreneurs. The overall objective of the research is to identify the changes resulting from the project intervention (EMP-2) using sustainable livelihood approach and to find out the relationship between the livelihood assets and enterprise of SME owners. The researcher uses Sustainable Livelihoods Framework (SLF) to explore the human, social, financial, and physical and natural resource based assets that enable the poor to enhance their capabilities and reduce their vulnerabilities. A qualitative study is conducted by consenting the SME owners who were beneficiaries of the EMP-2. Unstructured and in-depth interviews were conducted; interviews were taped, transcribed and thematically analyzed by using NVivo 10. Data has been collected from three major regions of Mongolia which are Selenge Aimag, Khenti Aimag and Uvurkhangai Aimag. Out of 20 respondents, 8 belong to Selenge Aimag, 6 belong to Khentii Aimag and 6 belong to Uvurkhangai Aimag respectively. Results are extracted from Nvivo 10, word frequencies, word trees, results previews and qualitative model is generated with the help of Nvivo 10. Results clearly demonstrate that the EMP-2 project provided support in terms of financial capital, human capital, physical capital, social capital and natural capital and this improves the livelihoods of the small and business entrepreneurs in Mongolia. Findings of the study also illustrates that EMP-2 project ease out the funding’s and loan processes, provide training to their workers and resolve the issues in regards to water shortage and energy shortage. The results of this study can be used by the NGO’s and other charity organizations to go in Mongolia and introduce projects like EMP to provide support to SME owners so that their livelihood can improve and poverty can be reduced or eliminated. Keyword: EMP, SMEs, Mongolia, Livelihoods, Sustainable Livelihood Framework
Keywords: Economic development projects; Small business; Entrepreneurship; Sustainable development; EMP; SMEs; Mongolia; Livelihoods; Sustainable livelihood framework; Research Subject Categories::SOCIAL SCIENCES::Social sciences